2009
DOI: 10.1111/j.1475-6773.2009.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Demographics and Access to Health Care among U.S. Hispanics

Abstract: The results suggest that characteristics of the local population, including language and nativity, play an important role in access to health care among U.S. Hispanics, and point to the need for further study, including analyses of other racial and ethnic groups, using different geographic constructs for describing the local population, and, to the extent possible, more specific exploration of the mechanisms through which these characteristics may influence access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…Both language versions showed high levels of content validity and conceptual equivalency. The rigorous translation process and review of the Spanish version by experts found [27][28][29] Nevertheless, their range of education (6 to 22 years) suggests that the translated measure is relevant to a broad span of Spanish-speaking learners with a minimum of sixth grade education. These shortcomings will need to be addressed in future studies to determine the settings and populations in which use of the new instrument is most appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both language versions showed high levels of content validity and conceptual equivalency. The rigorous translation process and review of the Spanish version by experts found [27][28][29] Nevertheless, their range of education (6 to 22 years) suggests that the translated measure is relevant to a broad span of Spanish-speaking learners with a minimum of sixth grade education. These shortcomings will need to be addressed in future studies to determine the settings and populations in which use of the new instrument is most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Translation issues and years of schooling have been posited as barriers to adequate health assessment of Spanishspeaking Hispanics in the United States. [27][28][29] Proportions of participants with the presence of sleep disorders by categories showed consistency in reporting between language versions. Percentages of participants who report sleep disorders provide a foundation for prevalence rates among Spanish-speaking Mexican Americans.…”
Section: English Version Intercorrelationsmentioning
confidence: 99%
See 3 more Smart Citations